The Effect Of Online System Promotion And Service On The Decision To Purchase Economic Train Tickets (Case Study On Train Passengers At Lahat Station) - Merry Indah; Emila Sholiha; Markus Markus (Universitas Dehasen Bengkulu, 2026)
This study aims to determine how promotions and online system services partially and simultaneously influence the decision to purchase economy class train tickets (a case study of train passengers at Lahat Station). The sample size for this study was 44 respondents. The sampling method used was incidental sampling. This quantitative study employed multiple linear regression analysis, processed using SPSS, resulting in a regression equation . The results of this study indicate a significant effect between promotions and the decision to purchase economy class train tickets (a case study of train passengers at Lahat Station), and a significant effect between online system services and the decision to purchase economy class train tickets (a case study of train passengers at Lahat Station). The F-test indicates that promotions and online system services simultaneously influence the decision to purchase economy class train tickets (a case study of train passengers at Lahat Station).